Implementation of Firmware Based on Real-Time Operating System for Small Size League Robot - Freiberger, Andrei; Maximo, Marcos R. O. A.; Loubach, Denis (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This article presents the implementation of a real-time operating system (RTOS) on ITAndroids Small Size League (SSL) category robots, a significant advancement for the team's participation in the Robocup SSL. The transition to using the STM32H753BI microcontroller and FreeRTOS on the second-generation Mainboard enhances temporal predictability and de-terminism, crucial for real-time systems. This development allows more efficient task management, including motor control, kicker charging, telemetry transmission, and fault handling, leading to improved robot performance and reliability during matches. The detailed system description and task implementation showcase how the Mainboard efficiently handles various functions such as motor control in a constant rate, responsive kicking mechanisms, and real-time telemetry collection and transmission. The work contributes by proposing a real-time operating system for a robot designed to participate in the RoboCup Small Size League (SSL). Despite the implementation being dependent on our team's design decisions, the concepts presented here can be adapted by other teams.